Amh Polymorphisms and their association with traits indicative of sexual precocity in nelore heifers - Pierucci, Julia Cestari [UNESP]; Tonhati, Humberto [UNESP]; De Albuquerque, Lúcia Galvão [UNESP]; Cardoso, Diercles Francisco [UNESP]; De Abreu Dos Santos, Daniel Jordan [UNESP]; Freitas, Ana Cláudia [UNESP]; Barbero, Marina Mortati Dias; De Camargo, Gregório Miguel Ferreira; Braz, Camila Urbano [UNESP]; Gimenes, Lindsay Unno [UNESP] (Universidade Estadual de Londrina, 2019)
Anti-Müllerian Hormone (AMH) is a protein expressed in the gonads and related to ovarian follicular development. The aim of this study was to investigate the presence of polymorphisms in the AMH gene in a Nelore herd to analyze the genetic constitution of this population and to perform association studies with early pregnancy occurrence (EPO) and age at first calving (AFC). Phenotypic data consisted of verification of early pregnancy and age at first calving of 197 unrelated heifers exposed to the mating season and aged between 15 and 17 months (precocious group) and 24 months (non-precocious group). The “precocious” group consisted of 67 heifers with age at first calving of 26.5 ± 0.59 months, and the “non-precocious” group was composed of 130 heifers with age at first calving of 36.4 ± 0.99 months. All five exons of the AMH gene were amplified by Polymerase Chain Reaction (PCR) and sequenced. A total of three SNPs were identified in this study, all of them located in exon 5 (rs527023314, rs722016629, and rs134387246), the latter one positioned in the stop codon. All three SNPs identified in exon 5 characterized synonymous mutations. Only SNP rs134387246 exhibited a significant value (P ≤ 0.10) for EPO and AFC. The association study of SNP rs134387246 revealed an over-dominance effect (P = 0.056), and no additive effect was observed (P = 0.67). A reduction of 2.5 months (75 days) in the age at first calving of heterozygous heifers for the SNP rs134387246 was observed. For the first time, polymorphisms of the AMH gene were described in Nelore heifers and associated with sexual precocity traits.
Keywords: Age at first calving; Bos taurus indicus; Early pregnancy occurrence; Fertility; SNP